2010
DOI: 10.1007/s11099-010-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal development and associated photosynthetic performance of capsicum in response to differential light availabilities

Abstract: The mechanisms of capsicum growth in response to differential light availabilities are still not well elucidated. Hereby, we analyzed differential light availabilities on the relationship between stomatal characters and leaf growth, as well as photosynthetic performance. We used either 450-500 μmol m -2 s -1 as high light (HL) or 80-100 μmol m -2 s -1 as low light (LL) as treatments for two different cultivars. Our results showed that the stomatal density (SD) and stomatal index (SI) increased along with the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
(33 reference statements)
3
14
1
Order By: Relevance
“…1). Control plants had a photosynthetic efficiency comparable to values obtained in previous studies on C. annuum 'Zhongjiao' and 'Niujiao' (Fu et al, 2010). The light-saturated photosynthetic rate was reduced significantly at low N and 7 dS · m -1 salinity levels to 47% and 64%, respectively, of the observed control rate (Table 2; Fig.…”
Section: Resultssupporting
confidence: 83%
“…1). Control plants had a photosynthetic efficiency comparable to values obtained in previous studies on C. annuum 'Zhongjiao' and 'Niujiao' (Fu et al, 2010). The light-saturated photosynthetic rate was reduced significantly at low N and 7 dS · m -1 salinity levels to 47% and 64%, respectively, of the observed control rate (Table 2; Fig.…”
Section: Resultssupporting
confidence: 83%
“…This in turn severely limits the photosynthetic rate as evident from the 30–50% decrease in CO 2 assimilation in transgenic plants. Such an effect of reduced stomatal density and conductance on CO 2 uptake, photosynthesis, and productivity has also been reported in several previous studies in various plants (Freeland, 1948; Heichel, 1971; Fu et al , 2010). Conversely, stomatal density is markedly affected by the environment and hence an effect of reduced photosynthesis on stomatal density reduction cannot be ruled out.…”
Section: Discussionsupporting
confidence: 84%
“…However, our values were generally higher than those reported by Borisev et al (2012) who also reported that the WUE of indoorgrown C. annuum variety (nine) varied less than that of field-grown plants (3.2-3.5 and 2.3-3.9, respectively). The WUE of Capsicum is reportedly impacted by irradiance; WUE was higher when plants were grown under high irradiance (400 mmol • m -2 • s -1 ; 2.2) compared to low irradiance (200 mmol • m -2 • s -1 ; 1.8) (Fu et al, 2010). However, irradiance in our study was 1000 mmol • m -2 • s -1 ; therefore, it would be considered high.…”
Section: Discussioncontrasting
confidence: 52%